Fitness Ability, Skills and Body Measurements for Selecting Elite Handball Players in Jordan - Taiysir Mansi; Abedesalam Jaber; Rami Halaweh (Sultan Qaboos University, 2013)
The purpose of the study is to construct standards for some fitness ability, skills and body measurements for selecting talented boys on handball centers in Jordan. The study samples were randomly selected and consisted of 152 male students (mean age = 15,82). Four physical tests were used: Speed (Sprint dash: 30-m), legs explosive strength (standing long jump), arms explosive strength (ball throw), flexibility, skills of passing and receiving coordination, and zig zag dribbling. Body measurements: height, weight and breadth of the palm and arms width were taken. Data were analyzed using arithmetic mean, standard deviation, percentage, percentile rank and coefficient of warping degree (means). The results revealed that physical abilities, skill abilities, and body and anthropometry measurements were not high. The research recommended that there is a need to adopt and use the standards produced by this study. Such standards would help in selecting handball players in Jordan.